The Consequences of the Religious Stratification of Multi-Religious Countries on the USA Example - NAZAROVA, KARINA A.; SOKOLOVSKIY, KONSTANTIN G. (The journal of contemporary issues in business and government, 2021)
Nowadays the problem of the society stratification is actual for any country. Multi- cultural states face the problem of religious stratification but it has not been studied and researched enough to find the proper solution to keep the society and population being united. Due to migration and immigration process and the globalization of the economy the process of religious stratification will concern any country and even those that have religious homogenous society. The consequences of this process and the solution to cope with this problem are proposed in this article. We took an example of the USA as it is multi-religious, cultural and race country, in which the stratification on any feature can be vividly seen in its harmful results. The analysis and studying of the achievement of status and life path traditions of the population in multi-national countries give a full picture of the religious stratification and its consequences for the society and show religion influences upon inequality.